SISTEM PERENCANAAN RUMAH CERDAS BERBASIS INTERNET OF THINGS - Masarrang, Maryantho; Sutapa, I Wayan; Rahman, Yuli Asmi (Foristek, 2023)
The Internet of Things concept is based on expanding the use and benefits of the internet by embedding controllers and sensors that can connect and share data continuously. A Smart Home prototype that can control door locks, lights and electrical pathways with easy control access. In this design, the device that will be used is an IoT-based controller, namely nodeMCU with connected actuators, namely servo motors, relays, and an IR sensor. The method used is to press a button on the web page and the system will respond to the request from the web page and convert it into an action, namely locking the door, or cutting off the electricity. To access it globally, by opening port forwarding on the router you can then access the web page of the smart home system prototype via the connected IP address so that the system can be controlled via the internet. With this system, it is hoped that users can increase time efficiency.